The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1080/13607860412331323782
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of everyday stress on the episodic memory test performances of young, mid-life, and older adults

Abstract: This research explored the differential association of everyday stress with the episodic memory test performances of young, mid-life, and older adults. Participants included 98 community-dwelling adults ranging in age from 19-89 years. Everyday stress was assessed via the Perceived Stress Scale and the Elder Life Stress Inventory. A brief battery of episodic memory tasks was administered which included tests of Logical Memory, Verbal Paired Associates, Digit Symbol Substitution, and Digit Symbol Incidental Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
2
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 45 publications
5
66
2
6
Order By: Relevance
“…findings are consistent with observational epidemiological studies(VonDras et al 2005 ;Johansson et al 2010), where self-perceived stress was found to be associated with cognitive impairment. The dose-response relationship between self-perceived stress and Mini Mental State Examination (MMSE) performance.…”
supporting
confidence: 89%
“…findings are consistent with observational epidemiological studies(VonDras et al 2005 ;Johansson et al 2010), where self-perceived stress was found to be associated with cognitive impairment. The dose-response relationship between self-perceived stress and Mini Mental State Examination (MMSE) performance.…”
supporting
confidence: 89%
“…Perceived stress may be particularly informative in healthy community samples such as the current study, where endorsement of depression symptoms may be low. Other research suggests that perceived stress may also influence objective memory and executive function performance among older adults (VonDras et al, 2005). One biological mechanism that may link perceived stress to subjective and objective memory deficits is the potentially detrimental effects that stress-induced glucocorticoid secretion can have on the hippocampus, which is a critical brain region for learning and memory (Lupien et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Email: guy.potter@duke.edu events and the associated experiences of stress, depression, or anxiety may introduce task-irrelevant distractions into daily life in a manner that challenges the efficient use of cognitive resources, which thereby may contribute to the perception of memory difficulty. This idea is supported by one finding that higher levels of perceived stress and stressful life events were associated with greater age-related differences on objective measures of episodic memory and executive functions (VonDras, Powless, Olson, Wheeler, & Snudden, 2005). Together, these results raise the question of how stressful events and perceived stress contribute to subjective memory complaints in older adults, which is important because the negative effects of stress be may modifiable by cognitive and behavioral interventions.…”
mentioning
confidence: 83%
“…To look for such effects, we assessed logical memory (i.e., memory for the details of a story), which has previously been used to demonstrate performance differences due to stress (e.g., VonDras, Powless, Olson, Wheeler, & Snudden, 2005) and medical malingering (e.g., Langeluddecke & Lucas, 2003). We predicted that logical memory would not be enhanced by action video game experience, thus revealing any motivational differences between the groups.…”
Section: Experiments 2: Logical Memorymentioning
confidence: 99%